The relationship between genre-based English learning material to Indonesian learner's motivation and achievement - Gayatri, Bertha Resivia; Ciptaningrum, Dyah Setyowati; Astutik, Yunik (Department of Applied Linguistics, FBSB, Universitas Negeri Yogyakarta, 2020)
Achieving an effective learning activity requires appropriate teaching materials in the learning process. Yet, there are some problems in the preparation of learning materials to teach that affect delivering the materials in the learning process. This paper is aimed to examine the impact genre-based as a learning material which is able to motivate learners in learning with interesting activity for learning process to improve learners' writing achievement. The finding of this study shows that the learner's motivation and achievement were improved. Also, there were a strong relationship between the usability of Genre-based learning materials to learner's motivation and achievement. The result of this study is expected going to be applicable for teachers who want to shift their teacher-centered learning style to be learner-centered style in writing activities. Also, it is for the reader who is concerning to English learning media and learners motivation.